THE EFFECT OF WORK STRESS ON WORK PRODUCTIVITY IN HEALTH SERVICES LAMPUNG PUSKESMAS - M. Junaidi; Ketut Partayasa; Linda Septarina; Suarni Norawati (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
After the pandemic, the people of Lampung continued to improve themselves with the government's program of giving vaccinations to all Lampung people which turned out to be difficult in activities that were so complex that it could cause work stress. The quality of Human Resources and the productivity of employees who provide the best service to the community cutting the virus chain are the most important things. One of the strategies implemented to increase employee productivity is to prevent work stress on employees, namely by implementing the MOSB program (Providing Healthy Food, Regular Exercise, Spiritual Showers, Bonuses). The purpose of this study was to examine the empirical relationship between work stress and the productivity of Puskesmas employees. This study also examines the effect of work stress on the productivity of Puskesmas employees. Respondents in this study were Bandarlampung Health Center employees. The analytical method uses relevant quantitative data with simple linear regression. The findings show that through the MOSB program it can prevent work stress from occurring thereby significantly increasing the work productivity of Puskesmas employees. Keywords: Work Stress, Employee Productivity, Health Services